Long-term morbidities in stroke survivors: A prospective multicenter study of Thai stroke rehabilitation registry - Kuptniratsaikul V. (2014)
Background: Stroke-related complications are barriers to patients' recovery leading to increasing morbidity, mortality, and health care costs, decreasing patient's quality of life. The purpose of this study was to quantify incidence and risk factors of stroke-related complications during the first year after discharge from rehabilitation ward. Methods. A prospective observational study was conducted in nine tertiary-care rehabilitation centers. We evaluated the incidence of morbidities during the first year after stroke, including musculoskeletal pain, neuropathic pain, pneumonia, deep vein thrombosis (DVT), pressure ulcer, spasticity, shoulder subluxation, joint contracture, dysphagia, urinary incontinence, anxiety and depression. The complications at discharge and at month-12 were compared using the McNemar test. Univariate analysis and multiple logistic regression analysis by forward stepwise method were used to determine factors predicting the complications at month-12. Results: Two hundred and fourteen from 327 patients (65.4%) were included. The age was 62.1 ± 12.5 years, and 57.9% were male. In 76.8% of the patients at least one complication was found during the first year after stroke. Those complications were musculoskeletal pain (50.7%), shoulder subluxation (29.3%), depression (21.2%), spasticity (18.3%), joint contracture (15.7%) and urinary incontinence (14.4%). Other complications less than 5% were dysphagia (3.5%), pressure ulcer (2.6%), infection (1.5%), and neuropathic pain (3.0%). Nearly 60% of patients with complications at discharge still had the same complaints after one year. Only 7.6% were without any complication. Morbidity was significantly associated with age and type of stroke. Using multiple logistic regression analysis, age and physical complications at discharge were significant risk factors for physical and psychological morbidities after stroke respectively (OR = 2.1, 95% CI 1.2, 3.7; OR = 3.1, 95% CI 1.3, 7.1). Conclusion: Long-term complications are common in stroke survivors. More than three-fourths of the patients developed at least one during the first year after rehabilitation. Strategies to prevent complications should be concerned especially on musculoskeletal pain which was the most common complaint. Physical complications at discharge period associated with psychological complications at 1 year followed up. More attention should be emphasized on patients age older than 60 years who were the major risk group for developing such complications. © 2013 Kuptniratsaikul et al.; licensee BioMed Central Ltd.